Revaluation of historical heritage. The Acho square mid-18th century - Barrera Camarena, Henry (2015)
In the present article, we propose the reassessment of the role of the Plaza Firme de Toros de Acho as national heritage by analyzing its historical significance, highlighting the role it played during the Bourbon urban reform in the mid 18th century and the type of architecture of its buildings. Thus, we seek to emphasize the transcendence of one of the oldest bullrings in the world and the urgency that there is for its revaluation, despite the morphological changes that it may have suffered in the time being. Considering this, the article will focus on the study of the building itself, without participating on the heated debate that currently takes place regarding the ban of bullfights, because, beyond it, is the conservation of a monumental relic that needs to be recovered and reinserted into the rich history of the city of Lima.